Environmental Responsibility, Strategy, and Competitive Advantage: Mediating Effect of Environmental Innovation - Al-Kahtani, Shaker M.; Senan, Nabil Ahmed Mareai; Alanazi, Ibtisam Dhuwayhi (International Journal of Energy Economics and Policy, 2024)
This study recognizes that corporate environmental responsibility (CER) can be put into practice in both tactical and strategic ways. Companies often embrace environmental responsibility (ER) as a commitment to the environment as they deal with constraints on their resources while seeking competitive advantages (CAs). Companies are under tremendous pressure to fulfill their social and environmental responsibilities because of accelerating environmental issues. This study uses environmental innovation (EI) as a mediating variable to study the relationship between ER, environmental strategy (ES), and CAs. The study also attempts to understand how EI affects companies’ ability to compete. This paper fills the gap in the relevant literature where there is insufficient evidence regarding the practices of ER, ES, eco-innovation (EN), and competitive advantage (CA). This is due to the growing trend of EN and the resulting increase in research interest. A questionnaire was conducted on 45 of the largest local and foreign companies operating in the Republic of Yemen to achieve the objectives of the study. 250 survey questionnaires were distributed. Descriptive and inductive statistics, including structural equation modeling using Smart Plus 4 software, were used to analyze the data. The results of the study showed that the studied companies used EI strategies to a reasonable extent. We discovered a positive effect and relationship between ER and ES, as independent variables, and EI. We also discovered a direct positive effect and relationship between EN and CA. In addition, we concluded that there is a positive influence relationship and a mediating relationship between CA using EI as a mediating variable and ER and ES as independent variables.